2021
DOI: 10.3390/met11040627
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations and Experimental Study of H+-Irradiated Zr/Nb Nanoscale Multilayer System

Abstract: Nanoscale multilayer coating (NMC) based on Zr/Nb layers (100/100 nm) before and after H+ irradiation was investigated by combining experimental techniques with first-principles calculations. Detailed studies of structural and phase state and defect structure of Zr/Nb NMC were performed using methods of transmission electron microscopy, X-ray structural analysis, glow discharge optical emission spectrometry, and the Doppler broadening spectroscopy using variable energy positron beam. The first-principles calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 55 publications
5
20
0
1
Order By: Relevance
“…Previously, in Reference [15], we showed that the use of such pulsed beams makes it possible to increase the resistance of nitride ceramics to helium swelling by changing the dislocation density and crystallite size in the modified near-surface layer. Another way to reduce the rate of helium accumulation and subsequent swelling is to create multilayer coatings consisting of amorphous and crystalline layers of oxides or nitrides [21][22][23]. This method is based on the effect of the appearance of interfaces between crystalline and amorphous layers, which lead to the retention of implanted helium near the boundaries and a decrease in the rate of its agglomeration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, in Reference [15], we showed that the use of such pulsed beams makes it possible to increase the resistance of nitride ceramics to helium swelling by changing the dislocation density and crystallite size in the modified near-surface layer. Another way to reduce the rate of helium accumulation and subsequent swelling is to create multilayer coatings consisting of amorphous and crystalline layers of oxides or nitrides [21][22][23]. This method is based on the effect of the appearance of interfaces between crystalline and amorphous layers, which lead to the retention of implanted helium near the boundaries and a decrease in the rate of its agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…The basis for this hypothesis was a number of experimental works [14][15][16][17][18][19][20] aimed at studying the applicability of ionizing radiation to increase the radiation resistance of materials, as well as studying the mechanisms of radiation hardening of the near-surface layer of ceramics, steels, and multilayer coatings. Therefore, for example, in a number of works, the effect of radiation hardening at irradiation with high-precision pulse beams of near-surface layers of refractory materials and ceramics is considered [14][15][16][17][18][19][20][21][22]. The authors of these works call the main hardening mechanism changes in dislocation density and amorphization processes, followed by the formation of amorphous inclusions in the structure of the near-surface radiation-modified layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV-inert film (Kapton, aluminized mylar) Lead-based materials Si cells, gallium arsenide solar cells Low-temperature curing epoxy resin [100] Zr/Nb nanoscale multilayer coatings [101]a)…”
Section: Radioresistancementioning
confidence: 99%
“…Однако, границы зерен являются не стабильными стоками для дефектов, при интенсивном радиационном воздействии и высоких температурах возможен процесс рекристаллизации и уменьшение их объемной плотности. С данной точки зрения более стабильны гетерогенные структуры, такие как наноразмерные многослойные металлические системы [3,4]. Особый интерес представляют Zr/Nb системы, ввиду низких сечений захвата нейтронов, хороших механических и коррозионных качеств, положительной энтальпии смешивания -4 КДж/моль, что должно обеспечивать высокую структурную стабильность при интенсивных радиационных воздействиях с высокими дозами облучения.…”
Section: национальный исследовательский томский политехнический униве...unclassified